Porcine Model to Study Mechanisms of Early Filling in the Left Ventricle - Burrowes, Lindsay; Satriano, Alessandro; Tyberg, John V.; Shrive, Nigel (CMBES Proceedings, 2016)
During diastole the left ventricle (LV) fills with blood in two phases, late filling and early filling. Late filling, resulting in the mitral flow “A-wave”, is a result of left atrial contraction. Early filling, manifest as the “E-wave”, is thought to be substantially due to diastolic suction (DS), a phenomenon where the LV aspirates blood and fills itself, independent of atrial activity. Efficient filling of the ventricle is important for the heart to adjust to varying demands. Before studying a sick heart, we must first understand the mechanisms of filling in a healthy heart. To study DS, we invasively measured pressure in a porcine model and used cardiac MRI to evaluate LV cavitary volume and in-flow (velocity). Here, we demonstrate that DS does exist and can be quantified using two different methods. The volume of filling due to DS (VDS) was defined as the volume of filling from mitral valve opening (MVO) until minimum LV pressure (PLVmin) in the pressure-volume (PV) loop. There was a negative slope in the PV relationship between the time of MVO and PLVmin. The negative slope suggests the ventricle is relaxing faster than it is able to fill thus aspirating blood into itself (Katz, 1930). Using Wave Intensity Analysis (Parker & Jones, 1990), the intensity of the backwards decompression wave was determined and the total energy of the wave after MVO was calculated. This indicates the energy of the ventricle at the end of ejection which then assists in drawing blood into the ventricle.